Proses Penyelesaian Perkara Korupsi Atas Putusan Pidana Kedalam Putusan Perdata (Studi Kasus Di Pengadilan Negeri Sragen) - Husna, Ummul, Nuswardhani, S.H, S.U (2016)
There is a case of corruption committed by the Defendant which the plaintiff would ask for money damages against the Defendant but the Defendant refused to pay the compensation money. This study aims to determine the consideration of the judge in determining the civil verdict on the corruption cases that have been sentenced to a criminal verdict, to determine the legal consequences of criminal decisions handed down after the civil verdict on corruption cases. The research method using descriptive normative approach.Using this type of primary data and secondary data.Data collection techniques used through the study of literature, documentation, questionnaires and interviews.By using qualitative data analysis. The results showed that the consideration of the judge looks at the evidence at trial, the legal consequences for the defendants in the trial the plaintiff can prove the argument of the lawsuit, the plaintiff is granted, the defendant was sentenced to pay compensation to the Plaintiff.